2010
DOI: 10.1371/journal.pone.0013417
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Striatal Specific Phosphodiesterase PDE10A Ameliorates Striatal and Cortical Pathology in R6/2 Mouse Model of Huntington's Disease

Abstract: BackgroundHuntington's disease is a devastating neurodegenerative condition for which there is no therapy to slow disease progression. The particular vulnerability of striatal medium spiny neurons to Huntington's pathology is hypothesized to result from transcriptional dysregulation within the cAMP and CREB signaling cascades in these neurons. To test this hypothesis, and a potential therapeutic approach, we investigated whether inhibition of the striatal-specific cyclic nucleotide phosphodiesterase PDE10A wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 57 publications
9
125
1
1
Order By: Relevance
“…5 to 8). Reagents that activate the cAMP/PKA pathway in the striatum are therefore beneficial in HD mice, as was reported previously (11,20,34). This cross talk between PKA and the proteasome might be brain area specific or disease stage dependent.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…5 to 8). Reagents that activate the cAMP/PKA pathway in the striatum are therefore beneficial in HD mice, as was reported previously (11,20,34). This cross talk between PKA and the proteasome might be brain area specific or disease stage dependent.…”
Section: Discussionsupporting
confidence: 53%
“…The cAMP/PKA pathway has long been recognized as fundamentally important to HD pathogenesis and for drug development in HD (11,12,15,20). In the present study, we showed that the activity of PKA in the striatum of two HD mouse models was lower than that observed in their littermate controls (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…(Sancesario et al, 2004;, and Huntington's disease (HD) (Hebb and Robertson, 2007;Giampà et al, 2009Giampà et al, , 2010Kleiman et al, 2011). All of these disorders are associated with abnormal corticostriatal neurotransmission (Shepherd, 2013), a function strongly influenced by striatal cyclic nucleotide signaling (Greengard, 2001).…”
Section: Implications For the Treatment Of Neurological And Psychiatrmentioning
confidence: 99%
“…Selective inhibitors of PDE10A have been reported to be efficacious in preclinical rodent behavioral models of schizophrenia, such as phencyclidine-stimulated hyperlocomotor activity, prepulse inhibition model, and conditioned avoidance response (Siuciak et al, 2006(Siuciak et al, , 2008Grauer et al, 2009). Moreover, the PDE10A inhibitor 2,pyrazol-3-yl]phenoxy]methyl]quinoline) has been demonstrated to ameliorate pathology and locomotor behavior in rat and R6/2 mouse models of Huntington's disease (Giampà et al, 2009(Giampà et al, , 2010.…”
Section: Abbreviationsmentioning
confidence: 99%